Genetic analysis of latrophilin in the toxicity of combined latrotoxins for C. elegans - Adenle, Ademola A. (2010)
Black widow spider venom (BWSV) contains high molecular weight proteins called latrotoxins (LTX) that induce catastrophic neurotransmitter release from nerve terminals, and one toxin, α-latrotoxin, is known to bind with high affinity to three neural proteins in mammals, including latrophilin (lat-1) a member of the class B family of G-protein coupled receptors. We have established C.elegans as a model organism to study the function of the binding protein, lat-1 and its role in regulating neurotransmitter release by latrotoxins. However, a lat-1-knockout worm is required for determining the function of the lat-1 gene. The lat-1(ok1465) allele has a deletion of the lat-1 gene, and ~95-98% of lat-1(ok1465) homozygous worms arrest or die before adulthood, with only ~2-5 adult offspring per animal. Micro-injection of the B0457 cosmid, that contains the full sequence of the lat-1 gene, or the lat-1a cDNA rescued the lethality of the lat-1 worms, thereby showing that lat-1 gene is responsible for the developmental lethality in these worms. Expression of the marker, GFP, under the control of the lat-1 promoter showed that there was expression of GFP during epithelial morphogenesis, and strong expression in the gut from the three-fold stage through to larval stages. The concordance between the site of expression of lat-1::gfp, with the sites of embryonic defects (epithelial enclosure defects; defective attachement of gut) in lat-1(ok1465) animals, provides further evidence that lat-1 is essential for embryonic and larval development. Deletion mutants of lat-1a were constructed to examine the role of domains of this protein. Deletion of sequences after the 4xCys domain of lat-1a did not affect the ability to rescue lethality in the lat-1 worm, while deletion of the C-terminus to the seven transmembrane domain impaired the ability of lat-1a to rescue lat-1 worms, and further deletion of six of seven transmembrane domains (the TM1 construct) yielded a construct that was unable to rescue lat-1 worms. These data suggest an important role for intracellular sequences and seven transmembrane in lat-1a signalling. It was proposed that TM1 could decoy ligand, without causing intracellular signalling. In agreement, the TM1 construct caused a mild phenocopy of the lat-1(ok1465) mutant in wild-type worms, whereas full-length, or non-ligand binding variants of lat-1a caused no such effect. To investigate the putative ligand-binding domain of lat-1a, deletion of residues 62-147 (ΔGBL), 62-250 (ΔHRM) and 62-487 (ΔN) was investigated; while the ΔN construct was incapable of rescuing lat-1(ok1465) worms, deletion of ΔGBL had a minor effect on the ability of lat-1 to rescue the null worms, while ΔHRM had a more marked effect. These data are consistent with a model whereby residues 147-487 are required for ligand binding, and the seventransmembrane and intracellular domains transmit a signal to the inside of the cell. Combined latrotoxins was highly toxic to wild-type C.elegans (LD50 ~4ng/ml), whereas the lat-1 worms were highly (>105-fold) resistant to combined latrotoxins. Lat-1 worms that were transgenic for B0457cosmid, or lat-1a cDNA, were as sensitive to combined latrotoxins as wildtype worm. Truncation of the C-terminus of lat-1a to TM1 yielded worms that had 105-fold resistance to combined latrotoxins, compared to wild-type; thus the intracellular domain of lat-1 is required for mediating combined latrotoxins toxicity. The deletion of galatactose-binding lectin (ΔGBL) in N-terminus lat-1a was sensitive as wild-type, but deletion of hormone receptor motif (ΔHRM) in N-terminus lat-1a showed a reduced sensitivity to combined latrotoxins by ~105-fold. These data showed presence of lat-1 gene was responsible for the rescue of lat-1 worms or toxicity of combined latrotoxins in lat-1 worms, and the absence of lat-1 gene was responsible for the lethality of lat-1 worms and resistance to combined latrotoxins in lat-1 worms.